2005
DOI: 10.1081/pte-200048712
|View full text |Cite
|
Sign up to set email alerts
|

Slow Release of Urea as a Source of Nitrogen from Some Acrylamide and Acrylic Acid Hydrogels

Abstract: Some hydrogels based on acrylamide and acrylic acid were synthesized by c radiation using N,N methylenebisacrylamide as cross-linker. Fourier transform infrared spectroscopy (FT-IR) and scanning electron microscope (SEM) were used for the characterization of the prepared hydrogels. Thermal gravimetric analysis (TGA) was used to investigate the thermal stability. The water uptake, % of these hydrogels depends on acrylamide=maleic acid (AAm=MA) and acrylic acid=maleic acid (AAc=MA) comonomers ratio. The highest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 12 publications
(6 reference statements)
1
7
0
Order By: Relevance
“…Calculation of the diffusion coefficient D from the release rate K is possible: The value calculated for the diffusion coefficient D of urea in SSRNF hydrogel is about (2.4 ± 0.2)× 10 −6 cm 2 s −1 , which is in general agreement with the diffusion coefficients of urea in hydrogel, i.e. about 10 −5 –10 −6 cm 2 s −1 , as reported in the literature 31, 32…”
Section: Resultssupporting
confidence: 85%
“…Calculation of the diffusion coefficient D from the release rate K is possible: The value calculated for the diffusion coefficient D of urea in SSRNF hydrogel is about (2.4 ± 0.2)× 10 −6 cm 2 s −1 , which is in general agreement with the diffusion coefficients of urea in hydrogel, i.e. about 10 −5 –10 −6 cm 2 s −1 , as reported in the literature 31, 32…”
Section: Resultssupporting
confidence: 85%
“…In some polymer‐clay or polymer‐silica nanocomposites, it was reported that the strength of the hydrogel can be increased by incorporating a small amount of inorganic species . In comparison, similar amphoteric hydrogel structures without reinforcing inorganic components were usually very fragile especially on swelling . However, on further incorporation, strain generally decreased with the increase of strength.…”
Section: Resultsmentioning
confidence: 99%
“…Microwave-mediated biochar-hydrogel composites [52] Polyvinylpyrrolidone (PVP)/carboxylmethyl cellulose [53] Acrylamide and acrylic acid based hydrogels [54] Glutaraldehyde crosslinked chitosan-poly(vinylalcohol) hydogel [55] Borassus aethiopum starch and Maesopsis eminii hydrogels [56] Poly(acrylonitril)-based poly acrylic acid hydrogels, [57] Acrylamide and N-hydroxymethyl acrylamide hydrogel [58] Natural rubber, cassava starch crosslinked by glutaraldehyde hydrogel [59] Starch phosphate carbamate hydrogel [60] Starch cross-linked acrylic acid and acrylamide hydrogel [61] Poly (acrylamide-co-acrylic acid)/kaolin gel [62] Poly(maleic anhydride-co-acrylic acid) hydrogel [63] Poly(acrylic acid)/attapulgite/sodium humate composite hydrogel [64] Poly(acrylamide) and methylcellulose based hydrogels [65] N,N 1 -MBA crosslinked acrylic acid [12] Table 5.…”
Section: Typical Hydrogel Referencementioning
confidence: 99%